2015
DOI: 10.1038/ncomms9022
|View full text |Cite
|
Sign up to set email alerts
|

Rhomboid domain containing 1 promotes colorectal cancer growth through activation of the EGFR signalling pathway

Abstract: Rhomboid proteins perform a wide range of important functions in a variety of organisms. Recent studies have revealed that rhomboid proteins are involved in human cancer progression; however, the underlying molecular mechanism remains largely unclear. Here we show that RHBDD1, a rhomboid intramembrane serine protease, is highly expressed and closely associated with survival in patients with colorectal cancer. We observe that inactivation of RHBDD1 decreases tumor cell growth. Further studies show that RHBDD1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
74
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 48 publications
(56 reference statements)
7
74
3
Order By: Relevance
“…We find that RHBDL4 enhances ER-to-Golgi trafficking of the unprocessed, full-length TGFα but, contrary to a previous report16, does not directly contribute to its shedding. Unexpectedly, RHBDL4 regulates secretion of TGFα, and other cargoes, in extracellular microvesicles.…”
contrasting
confidence: 99%
“…We find that RHBDL4 enhances ER-to-Golgi trafficking of the unprocessed, full-length TGFα but, contrary to a previous report16, does not directly contribute to its shedding. Unexpectedly, RHBDL4 regulates secretion of TGFα, and other cargoes, in extracellular microvesicles.…”
contrasting
confidence: 99%
“…endoplasmic reticulum (ER)-associated degradation [21]. Recently, it has been shown that upregulation of RHBDL4 is linked to poor prognosis in colorectal cancer and that inactivation (by genetic methods) led to a decrease in growth of colorectal cancer cell lines [22]. The authors of this study concluded that the phenotype occurred through RHBDL4-mediated cleavage of transforming growth factor alpha (TGFa).…”
Section: Rhomboid Proteasesmentioning
confidence: 97%
“…Recent research revealed that these I-CLiPs play important roles in a variety of biological processes, including lipid homeostasis, EGF signaling, Notch signaling, stress response and bacterial sporulation and virulence (Nakayama et al, 2011;Kroos and Akiyama, 2013;Rawson, 2013;Schneider and Glickman, 2013;Lastun et al, 2016). I-CLiPs have been associated with several diseases such as Alzheimer's disease and Parkinson's disease (Walder et al, 2005;De Strooper et al, 2012;Song et al, 2015;Spinazzi and De Strooper, 2016).…”
Section: Introductionmentioning
confidence: 99%